KOMUNIKASI SELAMA PANDEMI COVID-19: BELAJAR DARI KEGAGALAN KOMUNIKASI RISIKO KESEHATAN YANG EFEKTIF - Aizun Najih (Universitas Tribhuwana Tunggadewi, 2020)
Abstract. Governments around the world can learn many important lessons from examining instances of ineffective communication with the public during the global coronavirus disease (COVID-19) panic. Ineffective government communication has resulted in much confusion and misunderstanding of the public, as well as severe errors in responding to growing health threats, causing catastrophic health and social repercussions for society and prolonging the pandemic. This article uses systems theory as a framework for analyzing government communication during the COVID-19 pandemic, providing recommendations for the government to establish an effective health risk communication strategy. The communication strategy encourages the delivery of relevant, accurate and sensitive information to key public groups, minimizing communication disruptions to guide desired coordinated action. The communication strategy can be applied locally, nationally and internationally.Keywords: health risk communication, government communication, pandemic, strategic communication, systems theory.Abstrak. Pemerintah di seluruh dunia dapat mempelajari banyak pelajaran penting dari memeriksa contoh komunikasi yang tidak efektif dengan publik selama kepanikan penyakit virus corona global (COVID-19). Komunikasi pemerintah yang tidak efektif telah mengakibatkan banyak kebingungan dan kesalahpahaman publik, serta kesalahan serius dalam menanggapi ancaman kesehatan yang terus berkembang, dan menyebabkan bencana kesehatan dan dampak sosial bagi masyarakat dan memperpanjang pandemi. Artikel ini menggunakan teori sistem sebagai kerangka untuk menganalisis komunikasi pemerintah selama pandemi COVID-19, memberikan rekomendasi kepada pemerintah untuk menetapkan strategi komunikasi risiko kesehatan yang efektif. Strategi komunikasi mendorong penyampaian informasi yang relevan, akurat, dan sensitif kepada kelompok-kelompok publik utama, meminimalkan gangguan komunikasi untuk memandu tindakan terkoordinasi yang diinginkan. Strategi komunikasi dapat diterapkan secara lokal, nasional, dan internasional.Kata kunci: komunikasi risiko kesehatan, komunikasi pemerintah, pandemi, komunikasi strategis, teori sistem.